Analisis Modal Sosial Mahasiswa di Himpunan Mahasiswa Prodi Pendidikan IPS (HMPIPS) FKIP Untan Periode 2022/2023 - Al Ikhsan, Ifnur; Buwono, Sri; Wiyono, Hadi; Ulfah, Maria; Karolina, Venni (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze social capital and examine further and in-depth related to social capital in the form of trust, norms, and student networks at HMPIPS FKIP Untan for the 2022/2023 period. This research uses a qualitative method with a case study approach. This research involved 10 students as research informants who were members of the Social Education Study Program FKIP Untan student association for the 2022/2023 period. Data collection techniques use observation, interviews, and documentation techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results are (1) HMPIPS FKIP Untan students for the 2022/2023 period have social capital of trust which is the key to the concept of trust which can be used as a trust parameter including Integrity, Competence, Consistency, Loyalty and Openness. (2) HMPIPS FKIP Untan students for the 2022/2023 period have social capital norms which then apply including norms such as Religious Norms, Moral Norms, Moral Norms, Habitual Norms, and Legal Norms. (3) HMPIPS FKIP Untan students for the 2022/2023 period have network social capital, namely the level of closeness and the level of togetherness. In conclusion, HMPIPS FKIP students for the 2022/2023 period have social capital in the form of trust, norms, and networks.